2009
DOI: 10.1111/j.1365-2230.2008.03118.x
|View full text |Cite
|
Sign up to set email alerts
|

Androgenic alopecia and insulin resistance: are they really related?

Abstract: Despite previous reports suggesting a link, our study found no significant relationship between insulin resistance and androgenic alopecia. Further studies are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
6
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 18 publications
4
41
6
2
Order By: Relevance
“…Our result coincided with (Nabaie et al) who could not demonstrate a significant difference between AGA cases and control group [20].…”
Section: Discussionsupporting
confidence: 93%
“…Our result coincided with (Nabaie et al) who could not demonstrate a significant difference between AGA cases and control group [20].…”
Section: Discussionsupporting
confidence: 93%
“…However, on contrary these studies in case controlled study from Egypt no association was observed between AGA and insulin resistance in young aged group including both gender [11]. In relation to this study in Nabaie et al study there was no difference in individual components of metabolic syndrome including serum fasting insulin level, fasting blood glucose, serum total cholesterol, triglyceride, high density cholesterol levels (HDL-C) and insulin resistance between the AGA and a control group [12].…”
contrasting
confidence: 46%
“…[910] The association between AGA and MetS may be gender-specific to females. [11] Furthermore, the association of MetS with increasing severity of AGA is inconclusive.…”
Section: Introductionmentioning
confidence: 99%